Evidence-Based Study Design for Hospital-Acquired Bacterial Pneumonia and Ventilator-Associated Bacterial Pneumonia. (11th January 2019) - Talbot, George H; Das, Anita; Cush, Stephanie; Dane, Aaron; Wible, Michele; Echols, Roger; Torres, Antoni; Cammarata, Sue; Rex, John H; Powers, John H; Fleming, Thomas; Loutit, Jeffrey; et al.
Abstract : Endpoints beyond mortality alone elucidate treatment benefits for hospital-acquired/ventilator-associated bacterial pneumonia patients. We developed a "mortality-plus" endpoint using a Medical Dictionary for Regulatory Activities database interrogation tool, incorporating important pneumonia complications (eg, respiratory failure). This endpoint has multiple applications in study analysis/interpretation. Abstract: Background: The US Food and Drug Administration solicited evidence-based recommendations to improve guidance for studies of hospital-acquired bacterial pneumonia (HABP) and ventilator-associated bacterial pneumonia (VABP). Methods: We analyzed 7 HABP/VABP datasets to explore novel noninferiority study endpoints and designs, focusing on alternatives to all-cause mortality (ACM). Results: ACM at day 28 differed for ventilated HABP (27.8%), VABP (18.0%), and nonventilated HABP (14.5%). A "mortality-plus" (ACM+) composite endpoint was constructed by combining ACM with patient-relevant, infection-related adverse events from the Medical Dictionary for Regulatory Activities toxic/septic shock standardized query. The ACM+ rate was 3–10 percentage points above that of ACM across the studies and treatment groups. Predictors of higher ACM/ACM+ rates included older age and elevated acute physiology and chronic health evaluation (APACHE) II score. Only patients in the nonventilated HABP group were able to report pneumonia symptom changes. Conclusions: If disease groups and patient characteristics in future studies produce an ACM rate so low (<10%–15%) that a fixed noninferiority margin of 10% cannot be justified (requiring an odds ratio analysis), an ACM+ endpoint could lower sample size. Enrichment of studies with patients with a higher severity of illness would increase ACM. Data on symptom resolution in nonventilated HABP support development of a patient-reported outcome instrument.